Mesothelioma and asbestosis in a young woman following occupational asbestos exposure: Short latency and long survival: Case Report - Perelman Marina; Kayser Klaus; Bitchatchi Enrique; Richter Elihu D (BMC, 2010)
Abstract A 27-year-old female white-collar worker was diagnosed in 1998 with mesothelioma eight and one-half years following first exposure as a bystander to debris in a site in which asbestos-containing building materials were being dismantled and rebuilding work took place. Prodromal back pain had been present for a year and a half. She underwent extrapleural pneumectomy and received an intrapleural infusion of cisplatin post-operatively. Exposure to asbestos was verified by contemporary reports and lung biopsy, which demonstrated asbestos bodies and microscopic interstitial fibrosis -conforming evidence for asbestosis. The patient is alive and well 12 years after diagnosis and 14 years after onset of symptoms. The combination of an extremely short latency period and long survival following occupational exposure to asbestos dust is unique.